Caracterização físico-química e avaliação sensorial de queijo tipo boursin de leite de cabras alimentadas com raspa de mandioca - Leal, Natalia Santos [UNESP] (2014)
The use of new sources of nutrition in the diet of ruminants milk producers is a common practice in the properties, however, its influence on sensory evaluation of dairy products is poorly studied. The objective of this study was to evaluate the physicochemical composition and sensory type Boursin cheese made from milk of goats exposed to increasing levels of substitution of corn by cassava in the diet. Were used eight Alpine goats in milk, divided into two Latin squares 4 x 4 subject to replacement levels 0, 33, 66 and 100% of the corn the diet for cassava. Individualized cheeses with milk from each goat for physico-chemical, yield and texture analyzes were prepared. For sensory analysis, the cheeses were produced from the milk of all animals of a treatment. Sensory analysis was performed for flavor and texture, with 50 taster untrained, using the test of difference from control and acceptance testing. The cheeses of the four treatments showed no differences in content fat, protein, total solids, acidity, moisture and ash, pH, yield and in texture parameters: gumminess, cohesiveness, hardness and chewiness. Sensory analysis indicated that the cheeses showed no difference in sensory acceptability of flavor and texture between the studied levels, indicating that the substitution of cassava was not perceived by the tasters. The milk produced by goats fed increasing levels of cassava replacing corn can be used in manufacture of cheese Boursin type without harming the physical and chemical composition, texture and sensory evaluation